دراسة بيئية لمركز معالجة المخلفات الصلبة في محافظة طرطوس (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
The environmental effects of the solid waste treatment center in Tartous Governorate were evaluated in this study. The study dealt with a number of basic elements in the design by providing detailed studies on the climate, the topography of the area around the center and the environmental condition. The physical and chemical properties of groundwater, surface and soil area were studied , Emphasis was also placed on social structure through a questionnaire distributed to the population in the region, which enabled access to proposals to reduce the spread of pollutants and improve health.status. Therefore, in the light of the results and data reached, mitigation measures have been put in place which will have a positive effect on the local environment, so that the effects of the center will be within acceptable limits. تم من خلال هذا البحث تقييم التأثيرات البيئية الناجمة عن مركز معالجة المخلفات الصلبة قي محافظة طرطوس على البيئة المحيطة، حيث تناول البحث عدداً من العناصر الأساسية في التصميم وذلك من خلال تقديم دراسات مفصلة عن المناخ وتضاريس المنطقة المحيطة بالمركز والحالة البيئية لها، كما تم دراسة الخصائص الفيزيائية والكيميائية للمياه الجوفية والسطحية وترب المنطقة،  واتم التركيز أيضاً على البنية الاجتماعية من خلال الاستبيان الموزع  على السكان في المنطقة مما مكن من الوصول إلى مقترحات كفيلة بالحد من انتشار الملوثات وتحسين الواقع الصحي. وعليه وعلى ضوء النتائج والمعطيات التي تم التوصل إليها وضعت الاجراءات التخفيفية بما ينعكس إيجاباً على البيئة المحلية بحيث تكون الآثار الناجمة عن المركز ضمن الحدود المقبولة.